Establishment and development of IBS in Malaysia - Fathi, Mohamad Syazli (2011)
Government of Malaysia has done a lot of effort to promote the usage of Industrialised Building System (IBS) as an alternative construction methods compare to conventional building system which is a more labour intensive. This paper describes the experiences of Malaysia in the adoption of industrialised building system (IBS) from the first level of establishment until its development along with various IBS definitions and categories. A comprehensive literature review from various sources was made to carry out the study. The idea of using IBS in Malaysia was first developed during the early sixties when the Minister of Housing and Local Government visited several European countries and evaluated their building systems performance. Then, in 1964, the government took a significant decision to implement one pilot projects using IBS concept which was launched on 1966. The findings of this research illustrated the timeline of IBS establishment and development in Malaysia along with the significant consequences of IBS implementation in construction industry. Therefore, it is hoped that the finding of this research could assist professional parties in construction industry in providing a better knowledge ground for improving decisions making to achieve the success of IBS construction projects implementation that could be along with attaining the project objectives in terms of predetermined objectives that are mostly within the time, specified budget and standard quality.